Genetic analysis for beta glucan, grain protein and other important traits in oats (Avena sativa L.) - Ahmad, Mushtaq; Zaffar, Gul; Razvi, S. M.; Dar, Z.A. (The Indian Journal of Genetics and Plant Breeding, 2016)
The parents and 45 F1 crosses (excluding reciprocals) in oats (Avena sativa L.) were analyzed genetically to generate information on combining ability, nature and magnitude of gene effects for beta-glucan, grain protein and physiological traits.The estimates of additive variance were higher in magnitude than their corresponding dominance genetic variance indicating the role of additive gene action for grain protein content and beta-glucan and for physiological traits like chlorophyll content, leaf area index and grain yield per plant that showed non additive gene action. Four parents SKO-207, SKO-208, SKO-209 and SKO- 212 were found to be good combiners for all traits studied. Twelve cross combinations viz.,SKO-204 X SKO-207,SKO-204 X SKO-208 ,SKO-205 X SKO-208, SKO-205 X SKO-212, SABZAR X SKO-208, SKO-207 X SKO-208, SKO-207 X SKO-209, SKO-208 X SKO-209, SKO-208 X SKO-212, SKO-209 XSKO-212, SKO-211 X SKO-212 and SKO-211 X SKO-213 exhibited desirable positive SCA effect for physiological traits, grain quality and yield.